Abstract C066: Matrix-M adjuvant – A promising adjuvant for preventative and therapeutic cancer vaccines development - Berit Carow; Linda Stertman; Jonathan Fix; Sarah Sellers; Raj Kalkeri; Cecilia Carnrot; Joyce S. Plested; Robert Walker; Ruxandra Draghia-Akli (Cancer Immunology Research, 2026)
Abstract A productive and antigen-specific immune response requires four essential components from a cancer vaccine: tumor antigens, formulations, immune adjuvants, and delivery vehicles. There is a growing need for safe and effective adjuvants tailored to cancer vaccines, which require strong cellular immunity. Matrix-M®, a saponin-based adjuvant derived from purified Quillaja saponaria bark, is known to enhance immune responses by promoting immune cell recruitment, Th1 polarization, and inflammasome activation. Early distribution of Matrix-M to draining lymph nodes contributes to the generation of long-lasting memory B cells and broad-based T-cell immunity1. Matrix-M–containing vaccines against some infectious diseases were shown to be safe and immunogenic across age groups2-7. Importantly, Matrix-M is compatible with multiple vaccine platforms. Beyond its established role in infectious disease vaccines, Matrix-M is being evaluated as a potential adjuvant for cancer immunotherapy. Recent findings reveal that Matrix-M enables antigen cross-presentation on MHC class I molecules by inducing a process called lysosomal membrane permeabilization (LMP)—a key event that facilitates antigen escape into the cytosol8. Following uptake by bone marrow–derived dendritic cells, Matrix-M and antigen show a high level of co-localization in the endosome, which subsequently enables efficient Matrix-M-induced cross-presentation. The localization of Matrix-M and antigen in the same endosome could potentially be enhanced by linking antigens to Matrix-M, which has been described for Matrix-M and avian influenza trimers9. The Matrix-M induced LMP supports the generation of cytotoxic CD8+ T cells, a critical component of anti-tumor immunity. These insights into the intracellular mode of action of Matrix-M promoting antigen cross-presentation and CD8+ T-cell priming highlight its potential to enhance the efficacy of prophylactic and therapeutic cancer vaccines.: References: 1) Carnrot, C. et al.Frontiers in Drug Delivery 3 (2023). 2) Datoo, M. S. et al. Lancet 403, 533-544 (2024). 3) Anez, G. et al. JAMA Netw Open 6, e239135 (2023). 4) Sang, S. et al. Wellcome Open Res 8, 450 (2023). 5) Venkatraman, N. et al. Lancet Microbe 6, 100868 (2025). 6) Shinde, V. et al. Lancet Infect Dis 22, 73-84 (2022). 7) Fries, L. et al. J Infect Dis 222, 572-582 (2020). 8) Zarnegar, B. et al. NPJ Vaccines 10, 184 (2025). 9) Patel, N. et al. Nat Commun 16, 6625 (2025). Citation Format: Berit Carow, Linda Stertman, Jonathan Fix, Sarah Sellers, Raj Kalkeri, Cecilia Carnrot, Joyce S. Plested, Robert Walker, Ruxandra Draghia-Akli. Matrix-M adjuvant – A promising adjuvant for preventative and therapeutic cancer vaccines development [abstract]. In: Proceedings of the AACR Immuno-Oncology Conference (AACR IO): Discovery and Innovation in Cancer Immunology: Revolutionizing Treatment through Immunotherapy; 2026 Feb 18-21; Los Angeles, CA. Philadelphia (PA): AACR; Cancer Immunol Res 2026;14(2 Suppl):Abstract nr C066.